THE IMAGE OF THE RIVER IN THE STORY OF U. HAMDAM “THE RIVER OF MY SOUL” (Scientific journal of the Fergana State University, 2023)
This article discusses the problem of the relationship between man and nature through the means of symbolization. The author shows the influence of the elements of water on the life of the protagonist. The image itself is considered in development by analyzing extensional relationships, as well as the psychological state of the character. The subject of the study is the river, her journey together with the author through the mazes of the soul.